Assessing controls on cross‐shelf phytoplankton and suspended particle distributions using repeated bio‐optical glider surveys. Issue 10 (22nd October 2016) - Henderikx Freitas, Fernanda; Siegel, David A.; Washburn, Libe; Halewood, Stuart; Stassinos, Erik
Abstract: Characterizing the space/time variability of bio‐optical properties is essential to understand the mechanisms that control cross‐shelf phytoplankton and suspended particle distributions in coastal waters. Approximately 400 high‐resolution cross‐shelf sections of bio‐optical properties collected with an oceanographic glider in the coastal Santa Barbara Channel, California, revealed complex relationships among optical properties and environmental conditions. Surface waves were found as a proximate control on suspended sediment variability for both inner and midshelves. Increases in phytoplankton abundances attributed to horizontal advection and upwelling events were observed only on episodic time scales. The lack of all‐encompassing linear relationships between environmental forcings and changes in cross‐shelf phytoplankton highlights the challenge of decoupling bio‐optical signals from their controlling processes in coastal zones where phytoplankton distributions are patchy, and where nearshore and offshore phytoplankton populations and suspended sediments often occupy the same portion of the water column. Clear relationships between runoff and productivity were not observed. Temporal variability of suspended particles and phytoplankton distributions were roughly independent from each other during stratified conditions. Synchronous increases in phytoplankton and suspended sediments were observed when associated with strong upwelling events that may induce mixing and promote productivity. The repeated glider sections illustrated many processes regulating phytoplankton and particle transport in the innershelf and showed the difficulty in establishing general connections between high‐frequency changes in optical properties and potential environmental forcings in a complex coastal environment. Key Points: Surface waves largely control changes in suspended particle load Local and regional processes control cross‐shelf phytoplankton distributions Glider data allowed space‐time characterization of nepheloid layers